A combined experimental and theoretical rationalization of an unusual zinc(ii)-mediated conversion of 18-membered Schiff-base macrocycles to 18-membered imine–amine macrocycles with imidazolidine side rings: an investigation of their bio-relevant catalytic activities. (22nd January 2021) - Chakraborty, Tonmoy; Mukherjee, Somali; Parveen, Rumana; Chandra, Arpita; Samanta, Debabrata; Das, Debasis
Abstract : Macrocyclic Zn(ii )-based Schiff base complexes exhibit significant phosphatase-like activity as well as high potential anticancer activity against breast cancer cells. Abstract : The 2 : 2 condensation reaction of 2, 6-diformyl-4-isopropyl phenol and N ′-(2-aminoethyl)ethane-1, 2-diamine leads to a macrocycle Schiff base ligand (H2 L ) with the N6 O2 chromophore, which in the presence of ZnX2 transforms into a new [2+2] 18 membered macrocyclic system (H2 L 1 ) with an N4 O2 chromophore and two exo-cyclic imidazolidine rings. The transformation of H2 L to H2 L 1 in the presence of ZnX2 is unique and was confirmed by single crystal X-ray diffraction. The structural analysis reveals that the transformation generates complexes with a dinuclear Zn(ii ) core connected to a ZnX3 moiety, leading to trinuclear species with the composition [Zn3 (L 1 )(X)5 ](CH3 OH)(H2 O). The complexes (X = Cl, 1 and X = Br, 2 ) are also isostructural, where the central and terminal Zn atoms have different coordination geometries (trigonal-bipyramidal and tetrahedral, respectively). A probable mechanistic pathway involved in the conversion of the 18-membered imine–imine macrocycles to 18-membered imine–amine macroycles with imidazolidine excyclic rings has been established by combined experimental and theoretical investigations. Both these complexes (1 and 2 ) were exploited to check their phosphatase-like activity using the disodium salt of 4-nitrophenylphosphate (4-NPP) as a model substrate in a 97.5% (v/v) DMF–H2 O mixture. The turnover numbers ( k cat ) of complexes 1 and 2 were calculated to be 17.905 and 14.235 s −1, respectively. The probable mechanistic pathway has been explored via trapping the intermediate species of the catalytic cycle by ESI-MS study. On considering the efficiency of the catalyst in phospho–ester bond hydrolysis, both complexes were tested for their anticancer activities on MDA-MB-231 (human breast cancer) and HeLa (cervical cancer) cell lines, as revealed by in vitro MTT assays. The better cell killing properties of complex 1 were further evidenced with the help of cell migration inhibition studies.